Impact of Company Size, Income on Share, Debt to Equity, Total Assets Revenue and Net Profit on The Kompas 100 Company Value Index - Wijaya, Evelyn; Ali, Zuriani; Hocky, Agus; Anton, Anton; Oliver, Winson (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This research aims to analyze the effect of company size, earnings per share, debt to equity ratio, total asset turnover and net profit margin on firm value on Kompas 100 index. The sample technique used were purposive sampling methods selected based on criteria. Thus, the number of samples were 59 companies. Data analysis technique used multiple linear regression analysis with SmartPLS 3. The results showed that company size, earnings per share, debt to equity ratio, total asset turnover have no effect on firm value while net profit margin has an effect on firm value. Thus, increasing NPM value will encourage a positive response from investors so that it will be encourage an increase on stock price and company value.